EFFECT OF PROACTIVO SORBENT ON BIOCHEMICAL PARAMETERS OF PIG BLOOD - Красніков, Сергій; Тарасенко, Людмила (Modern engineering and innovative technologies, 2024)
The paper deals with the effect of the sorbent ProActivo on the biochemical parameters of blood of experimental pigs. The relevance is due to the high concentration of mycotoxins in the feed used for feeding farm animals. The consumption of feed contamina